2015
DOI: 10.1111/ijfs.12798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrusion cooking on the dietary fibre content and Water Solubility Index of wheat bran extrudates

Abstract: Summary Instant study was an attempt to elucidate the suitability of wheat bran for extrusion cooking and to check the effect of different extrusion parameters on the dietary fibre profile as well as on water solubility index. Response surface methodology was used to optimise the extrusion parameters. From results, it was concluded that extrusion cooking had a positive effect on total and soluble dietary fibre. Whilst the insoluble dietary fibre decreased appreciably with the varying processing parameters, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 26 publications
5
71
0
1
Order By: Relevance
“…6a,b). Similar effects of feed moisture, screw speed and barrel temperature on WSI have been previously reported for rice-, maize-and millet flour-based extrudates (Suksomboon et al, 2011;Joshi et al, 2014;Rashid et al, 2015). It could be expected that higher feed moisture would reduce viscosity, decrease shearing effect and reduce the degree of dextrinisation of starch polymers resulting in decreased WSI.…”
Section: Water Solubility Index (Wsi)supporting
confidence: 72%
“…6a,b). Similar effects of feed moisture, screw speed and barrel temperature on WSI have been previously reported for rice-, maize-and millet flour-based extrudates (Suksomboon et al, 2011;Joshi et al, 2014;Rashid et al, 2015). It could be expected that higher feed moisture would reduce viscosity, decrease shearing effect and reduce the degree of dextrinisation of starch polymers resulting in decreased WSI.…”
Section: Water Solubility Index (Wsi)supporting
confidence: 72%
“…The fibre contents varied between 1.62 to 2.88%, with the least value recorded in sample extruded at 120°C barrel temperature, 20% moisture and 29.5% cowpea and the highest value observed in sample corresponding to 140°C barrel temperature, 15% moisture and 8% cowpea extrusion conditions. During extrusion cooking process, positive effects of the process parameters on the total and soluble fiber has been observed (Rashid, et al, 2015). Insoluble dietary fiber decreased apparently as the process parameters changes.…”
Section: Effects Of Processing Variables On Proximate Compositionmentioning
confidence: 99%
“…The swelling index, water uptake, and cooking loss were signifi cantly higher in samples with oat β-glucan fi ber powder compared to the control. Rashid et al (2015) examined the suitability of wheat bran for extrusion cooking and checked the eff ect of diff erent extrusion parameters on the dietary fi bre profi le as well as on the water solubility index. The results showed that extrusion cooking had a positive eff ect on total and soluble dietary fi bre.…”
Section: Thermal Processesmentioning
confidence: 99%